Assistance of Posyandu Cadres in Alleviating Stunting through the Corporate Social Responsibility (CSR) Program of the Modest KBC - Syuhana, Eka; Said, M. Mas'ud; Kurniati, Rini Rahayu; Fahrazaman, Fahrazaman; Rozi, Akhmad (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Stunting is a chronic malnutrition problem in toddlers. Indonesia has committed to reducing the stunting rate by 2024 to 14% according to WHO standards, namely below 20%. Various parties, including cadres and CSR, work to accelerate stunting reduction. The purpose of this service is to see how the process of assisting posyandu cadres in alleviating stunting through the CSR KBC BERMODEST program. The community service method used is Participatory Action Research (PAR) which is used to observe program implementation directly in the field. The result of this service is the implementation of a posyandu service workshop, nutritional stimulants, the creation of nutritional gardens, and the use of yards, which had an impact on increasing cadres' knowledge, reducing stunting rates, and fulfilling family nutrition.